Mobilization of Stroke Patients to Prevent Decubitus: A Systematic Review - Farid Rivai, Ahmad; Nur Imani, Meli (Ann Publisher, 2023)
Stroke is a disease or nerve disorder that occurs suddenly due to impaired blood flow to the brain. Stroke is known to cause various complications including the occurrence of decubitus wounds. Decubitus is one of the most frequent complications experienced by stroke patients. One of the therapies that can be given to prevent these complications is to take mobilization actions. The purpose of this literature review has been to analyze the provision of mobilization measures in stroke patients to prevent decubitus. The search method uses the Mendeley, PubMed, and Google Scholar databases between 2017 and 2021, with the keyword